Pharmacokinetics, mass balance, and metabolism of the novel potassium-competitive acid blocker JP-1366 in healthy Chinese adults following a single oral dose of [14C]JP-1366 - Liu, Xuemei; Deng, Decheng; Meng, Jian; Hu, Haitang; Zhuang, Quankun; Zhou, Xue; Fu, Long; Fan, Binke; Xu, Xueting; Huang, Qin; Chen, Xiaoyan; Hou, Fang (Frontiers in Pharmacology, 2025)
IntroductionJP-1366 (zastaprazan), a novel potassium-competitive acid blocker (P-CAB), was approved in South Korea in 2024 for treating erosive gastroesophageal reflux disease (GERD). This mass balance study characterized the pharmacokinetics, metabolism, excretion, and safety profile of JP-1366 in humans, supporting its further clinical development in China.MethodsSix healthy Chinese male adults received a single oral dose of 20 mg (100 μCi) [14C]JP-1366 under fasting conditions in this open-label Phase I study. Serial samples of blood, plasma, urine, and feces were collected and analyzed to determine Pharmacokinetic parameters, total radioactive recovery, metabolic fate, and excretion routes.ResultsJP-1366 was rapidly absorbed, with median Tmax values of 0.875 h observed for both the parent drug and total radioactivity in human plasma. The mean plasma elimination half-life (t1/2) was approximately 28 h for JP-1366-related material. Furthermore, the blood-to-plasma ratio of total radioactivity ranged from 0.561 to 0.645, indicating limited distribution of drug-related material into blood cells. Within 264 h post-dose, 94.3% of the administered radioactive dose was recovered through excretion, predominantly via feces (51.9%) and urine (42.4%). JP-1366 underwent extensive metabolism in vivo, generating 57 metabolites, while the parent drug remained undetectable in excreted samples. The principal metabolic pathways involved oxidations (Phase I) and the following glucuronidation (Phase I/II). JP-1366 exhibited a favorable safety profile, with no serious adverse events reported.ConclusionJP-1366 exhibited favorable pharmacokinetic properties characterized by rapid absorption, extensive metabolism, and predominant fecal excretion of drug-related material. The principal metabolic pathways involved oxidations and the following glucuronidation.Clinical Trial Registrationhttp://www.chinadrugtrials.org.cn/, identifier CTR20244931.